2006
DOI: 10.1021/jf050898h
|View full text |Cite
|
Sign up to set email alerts
|

Benzoxazinoid Allelochemicals in Wheat:  Distribution among Foliage, Roots, and Seeds

Abstract: In this study, the distribution of eight allelochemicals among the foliage, roots, and seeds of different wheat varieties is reported for two different sampling campaigns, corresponding to two consecutive years. The determination of benzoxazinoid derivatives was performed by combining pressurized liquid extraction--solid-phase extraction followed by liquid chromatography--electrospray mass spectrometry. To the authors' knowledge, there are no previous works about the content of allelochemicals in seed tissue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 20 publications
2
69
1
3
Order By: Relevance
“…International research on the allelo-pathy of wheat is active [7]. Research on wheat allelopa-thy has progressed rapidly from the initial phase of eva-luation of wheat allelopathy to the identification of wheat allelochemicals, the degradation of these compounds and, further, to the identification of genetic markers associated with wheat allelopathy [8,9].…”
Section: Allelopathic Effect Of Wheatmentioning
confidence: 99%
“…International research on the allelo-pathy of wheat is active [7]. Research on wheat allelopa-thy has progressed rapidly from the initial phase of eva-luation of wheat allelopathy to the identification of wheat allelochemicals, the degradation of these compounds and, further, to the identification of genetic markers associated with wheat allelopathy [8,9].…”
Section: Allelopathic Effect Of Wheatmentioning
confidence: 99%
“…Wheat (Triticum aestivum) is a potential allelopathic plant and its phytotoxic activity has been attributed to hydroxamic acids and related compounds (Wu et al, 2000a;Villagrasa et al, 2006) as well as phenolic acids (Wu et al, 2001). Wheat aqueous extracts were also allelopathic to pitted morning glory (Ipomoea lacunosa), common ragweed (Ambrosia artemisiifolia), and also to herbicide susceptible and resistant biotypes of annual ryegrass (Lolium rigidum) (Liebl & Worsham, 1983;Wu et al, 2000b, Wu et al, 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Correlations between higher benzoxazinoid concentrations and both Fusarium head blight (FHB) resistance (Soltoft et al, 2008) and yield in wheat (Silva et al, 2006) have been reported using a small number of cultivars. Wheat cultivars show significant differences in the total amount and proportions of benzoxazinoids found in thei r roots Villagrasa et al, 2006), leaves and grain (Villagrasa et al, 2006); although again only a small number of cultivars have been analysed. Whilst the correlation between benzoxazolinone levels and disease resistance has not been examined for Fusarium crown and root rot diseases, these defence compounds may also have an effect on these diseases if their concentrations are increased via traditional or molecular breeding approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Significant contributors to variation in benzoxazinoid levels are seasonal variability , the wheat cultivar, growth stage and plant age (Villagrasa et al, 2006), plant growth rate (Copaja et al, 1999), water stress, insect herbivory (Silva et al, 2006), light intensity (Ahman & Johansson, 1994), jasmonic acid signalling (Oikawa et al, 2001), and the presence of competitive weeds (Hasegawa et al, 2010).…”
Section: The Plant Tissue Concentrations Of Benzoxazinoidsmentioning
confidence: 99%
See 1 more Smart Citation